Strategi guru fikih dalam menangani fenomena distraksi gadget - Afifatinnisa, Seftiani; Rohman, Fathur (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2025)
Gadget distraction has become a serious challenge in Fiqh learning as it affects students’ focus, motivation, and participation. This study aims to analyze teachers’ strategies in overcoming learning obstacles caused by gadget use and to formulate solutions for improving the quality of Fiqh instruction. The research employs a qualitative method with a case study approach involving Fiqh teachers and several students. Data were collected through observation, interviews, and documentation, and then analyzed using a thematic descriptive approach. The findings indicate that teachers face challenges such as varying levels of student concentration, limited time to balance theoretical and practical learning, and the influence of social media. To address these issues, teachers implemented a no-gadget policy, developed more interactive teaching methods, and strengthened collaboration with parents. These strategies create a more conducive and effective learning environment.